Short-Chain Fatty Acids: A Potential Therapy for Colorectal Cancer - Chergui, Samia; Treml, Jack (Midwestern Journal of Undergraduate Sciences, 2024)
Short-chain fatty acids (SCFAs), primarily acetate, propionate, and butyrate, have garnered significant attention due to their anti-inflammatory properties within the human body.1 Expanding on these studies, recent research has revealed that SCFAs exhibit selective antitumor effects on colorectal cancer cells (CRC cells). The findings from these investigations have illuminated the influence SCFAs can have on the development and progression of colorectal cancer. These discoveries underscore the therapeutic potential SCFAs might offer in the management and treatment of colorectal cancer.